Development of Interactive Multimedia for Early Readers with Dyslexia at an Inclusive Elementary School in Malang City - Eka Mariana Sari; Wahyudi Siswanto; Mohammad Efendi (Department of Special Education, 2021)
Interactive multimedia is an electronic system containing images, animation, and an interaction between the media and students. It considered that dyslexic student needs multisensory methods and media in the learning process as well. This study aims designing interactive multimedia development for early reading of dyslexic student and finding out its effectiveness. The method used is William W. Lee and Diana L. Owens’ (2004) development model. The procedures are: (1) Assessment / Analysis, (2) Design, (3) Development, (4) Implementation and (5) Evaluation. The results of feasibility and effectiveness trials conducted by media experts scored 96% means